The Extraordinary Spirit of Green Chimneys : Connecting Children and Animals to Create Hope - Ross, Samuel B., Jr., 1928-2018 (Book collections on Project MUSE., 2011)
Green Chimneys is a nationally renowned US nonprofit organization that helps improve the lives of at-risk urban children by incorporating animals and environmental activities into their educational experiences. Founded by Dr. Samuel (Rollo) B. Ross, Jr.,?Green Chimneys Farm for Little Folk? opened its doors in 1948 with just eleven students. The property has since expanded to cover nearly seven hundred fifty acres in New York, and the school now serves almost two hundred students. Recognized as a worldwide leader in animal-assisted therapy and activities, Green Chimneys provides innovative and caring services for children and their families, as well as the animals with which they spend time. It targets its services at restoring emotional well-being and fostering independence. For over sixty years, Ross developed and operated this innovative and experimental year-round school, and he still remains integrally involved. This book recounts his experiences, sharing a lifetime of practical learning and insights to benefit and inspire all those who work with troubled children, and who believe in the healing power of the natural world.